Quality Control of Paint Tube Products Using Six Sigma and FMEA Methods - Khunaifi, Nasywa Shabrina; Safirin, Moch. Tutuk (Newinera Publisher, 2025)
PT XYZ is facingproduct quality challenges, especially visual defects in 25 kg pail tubes such as unmold tubes, jetting tubes, and IML on overlapping tubes with unmold tubes reached 55%. This study aims to analyze the main causes of defects in paint tube products at PT XYZ. The methods used are Six Sigma and FMEA with secondary data from the type of 25 kg tube defects in the last 3 months, involving 15 samples with 3 types of defects. The results show that material, mold, machine, and human factors contribute to defects. The Six Sigma value is 3.36, which is below standard. Recommendations for quality improvement are given to reduce the defect rate, with the highest RPN being 240 for unmold tubes.